Polyhydroxy structure orchestrates the intrinsic antibacterial property of acrylamide hydrogel as a versatile wound-healing dressing - Zhang, Lu; Tang, Yu-Jiao; Zhang, Wen-Qing; Wang, Jian; Cai, Yu-Jian; Qin, Tian-Yi; Zhang, Deteng; Wang, Zhao-Hui; Wang, Ya-Long (Frontiers in Bioengineering and Biotechnology, 2024)
Hydrogel is considered as a promising candidate for wound dressing due to its tissue-like flexibility, good mechanical properties and biocompatibility. However, traditional hydrogel dressings often fail to fulfill satisfied mechanical, antibacterial, and biocompatibility properties simultaneously, due to the insufficient intrinsic bactericidal efficacy and the addition of external antimicrobial agents.In this paper, hydroxyl-contained acrylamide monomers, N-Methylolacrylamide (NMA) and N-[Tris(hydroxymethyl)methyl] acrylamide (THMA), are employed to prepare a series of polyacrylamide hydrogel dressings xNMA-yTHMA, where x and y represent the mass fractions of NMA and THMA in the hydrogels. We have elucidated that the abundance of hydroxyl groups determines the antibacterial effect of the hydrogels. Particularly, hydrogel 35NMA-5THMA exhibits excellent mechanical properties, with high tensile strength of 259 kPa and large tensile strain of 1737%. Furthermore, the hydrogel dressing 35NMA-5THMA demonstrates remarkable inherent antibacterial without exogenous antimicrobial agents owing to the existence of abundant hydroxyl groups. Besides, hydrogel dressing 35NMA-5THMA possesses excellent biocompatibility, in view of marginal cytotoxicity, low hemolysis ratio, and negligible inflammatory response and organ toxicity to mice during treatment. Encouragingly, hydrogel 35NMA-5THMA drastically promote the healing of bacteria-infected wound in mice. This study has revealed the importance of polyhydroxyl in the antibacterial efficiency of hydrogels and provided a simplified strategy to design wound healing dressings with translational potential.